PERAN GURU PENJASORKES DALAM MENGATASI KENAKALAN SISWA (STUDI KASUS DI SMA NEGERI SE-KABUPATEN KENDAL) TAHUN 2013 (ACTIVE: Journal of Physical Education, Sport, Health and Recreation, 2015)
The purpose of this study to determine, describe, and analyze the role of teachers in addressing student misbehavior penjasorkes Public High School students in Kendal. This study used qualitative methods, the location of the research conducted in SMA se-Kendal. Research subjects in this study were penjasorkes teacher, principal, BK teachers and students. Data collected by using observation, interviews and documentation. The validity of using triangulation source. Data analysis using descriptive analysis model according to Miles and Huberman. Based on the results of research conducted and has been linked with the theory Suparwoto, et al. It can be concluded that the role of teachers penjasorkes (1) in terms of preventive prevent student misbehavior is good. (2) is good in terms of repression. (3) in terms of curative and rehabilitation are good. The conclusions that can be drawn from this research is the teacher's role in addressing delinquency penjasorkes students in SMA se-Kendal has been running both in terms of preventive, repressive and curative or rehabilitation)